The effects of plant extracts in feeding diet under different temperature on the physiological parameter and stress tolerance in striped catfish (Pangasianodon hypophthalmus) : - Tran, Thi Phuong Hang (Trường Đại học Cần Thơ, 2019)
To evaluate the effectiveness of plant extracts Psidium guajava and Phyllanthus amarus in feeding diet on physiological and stress parameters of striped catfish (Pangasianodon hypophthalmus) under different temperature, thereby contributing basic information for farming this species..